2020
DOI: 10.1111/apa.15204
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on retinal microvasculature, physical activity, sedentary behaviour and adiposity in children and adolescents

Abstract: Aim As retinal microvasculature (RMV) can be assessed non‐invasively, it presents an opportunity to examine the health and disease of the human microcirculation, as RMV alterations have been recognised as one of the earliest signs of cardiovascular risk. This review summarises current literature on the associations between physical activity (PA), sedentary behaviour (SB) and/or adiposity and RMV in children and adolescents aged 0‐18 years. Methods Six databases were searched (MEDLINE, Scopus, Web of Science, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 95 publications
(391 reference statements)
0
4
0
Order By: Relevance
“…Finally, it is important to note that this model presented fit indices that are more acceptable for boys than for girls. In this regard, there are several causes that could explain these findings, such as adolescence, which is characterized by a decrease in levels of physical activity, especially among girls [ 71 , 72 ]. This fact could be explained through the amount of daily physical activity performed by boys or girls [ 73 ], or the different types of physical activity practiced according to gender, which is associated with gender stereotypes, causing the rejection of certain activities due them being perceived as masculine [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is important to note that this model presented fit indices that are more acceptable for boys than for girls. In this regard, there are several causes that could explain these findings, such as adolescence, which is characterized by a decrease in levels of physical activity, especially among girls [ 71 , 72 ]. This fact could be explained through the amount of daily physical activity performed by boys or girls [ 73 ], or the different types of physical activity practiced according to gender, which is associated with gender stereotypes, causing the rejection of certain activities due them being perceived as masculine [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous studies where this difference was observed [ 9 , 68 ]. Studies also reported that males have higher levels of HRQoL [ 53 ] and physical activity [ 8 , 69 ]. Although the significance level in this study was not reached, values were also higher in boys than in girls.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that wider venules, narrower arterioles, and a lower AVR are related to a greater body mass index (BMI), larger waist circumference, and higher levels of sedentary behavior. In contrast, moderate-to-vigorous-intensity physical activity was associated with larger arterioles, narrower venules, and a higher AVR ( 20 ). Furthermore, other data demonstrated a strong relationship between retinal vascular calibers and obesity-induced hypertension.…”
Section: Introductionmentioning
confidence: 97%